Peroxisome-associated Sgroppino links fat metabolism with survival after RNA virus infection in Drosophila - Merkling, Sarah H. (Sci Rep, 2019)
The fruit fly Drosophila melanogaster is a valuable model organism for the discovery and characterization of innate immune pathways, but host responses to virus infection remain incompletely understood. Here, we describe a novel player in host defense, Sgroppino (Sgp). Genetic depletion of Sgroppino causes hypersensitivity of adult flies to infections with the RNA viruses Drosophila C virus, cricket paralysis virus, and Flock House virus. Canonical antiviral immune pathways are functional in Sgroppino mutants, suggesting that Sgroppino exerts its activity via an as yet uncharacterized process. We demonstrate that Sgroppino localizes to peroxisomes, organelles involved in lipid metabolism. In accordance, Sgroppino-deficient flies show a defect in lipid metabolism, reflected by higher triglyceride levels, higher body mass, and thicker abdominal fat tissue. In addition, knock-down of Pex3, an essential peroxisome biogenesis factor, increases sensitivity to virus infection. Together, our results establish a genetic link between the peroxisomal protein Sgroppino, fat metabolism, and resistance to virus infection.